PENGARUH PENCEMARAN LIMBAH INDUSTRI DAN DOMESTIK TERHADAP KUALITAS AIR WADUK DURIANGKANG - Hariyadi, Rosyid (Jurnal Teknologi Lingkungan, 2006)
Duriangkang resevoir (62.000.000 m ) physically located in DuriangkangCatchement Area of Batam island. The main function of Duriangkangresevoir is the water resources to support 78 % of drinking water supplyneeds of Batam Island with the processing capacity amounting to 3000liter/second. The main problem of Duriangkang Reservoir are : (1)industrial waste water from Batamindo Industrial Zone has been extremelypolluted with COD conten (134,61 mg/liter) exceeding the Waste WaterQuality Standard Group II (80 mg/liter), (2) domestically waste water fromdomestic activity in Duriangkang Catchment Area has also beenextremely polluted with BOD5 conten (58,22 mg/liter) exceeding theWaste Water Quality Standard Group II (50 mg/liter). This research tostudy influent of industrial waste water and domestically waste water tocarrying capacity of Duriangkang Reservoir.